Biochemical evaluation of root tubers and in vitro induced callus of adapathiyan (Holostemma ada-kodien K. Schum.) - Karmarkar, S.H.; Keshavachandran, R.; Augustin, A. (Journal of Tropical Agriculture, 2006)
Holostemma ada-kodien is a laticiferous climber belonging to the family Asclepiadaceae. The root tubers of the plant are medicinally important and are useful in opthalmopathy, orchitis, cough, burning sensation, stomachalgia, fever and to cure ’tridosha’. The medicinal properties of Holostemma are due to the presence of terpenoid sugars and amino acids. This study deals with the preliminary biochemical analysis of root tubers and in vitro induced callus of Holostemma. Comparative analysis of amino acids shows no alteration in the primary metabolism in the callus. The metabolism of production of terpenoid compounds in the callus however shows alteration.